Kinetic study of biomass activated carbon impregnated with copper (AC/Cu) as a photocatalyst in degradation of ammoniacal nitrogen - Hemaraj, SELVARAJ; Ibrahim, Yakub; Khairul Anwar, Mohamad Said; Mohamed Afizal, Mohamed Amin; Nur Syuhada, Ahmad Zauzi; Rubiyah, Baini (Materials Science and Engineering, 2025)
Generation of wastewater including leachate that contains ammoniacal nitrogen (AN) is increasing and requires urgent solution. The current status of the photocatalyst development for the degradation of this pollutant is promising but further improvement is desired. This study explored the possibility of using biomass activated carbon as a catalyst support to provide more surface area. Activated carbon from coconut shell was used to support 30 wt% copper catalyst in a wet impregnation procedure for the catalyst synthesis. Characterization of the photocatalyst (AC/Cu) was performed using scanning electron microscopy and energy dispersive X-ray (SEMEDX), BET surface area analysis, thermogravimetric and differential thermal analysis (TG/DTA), and Fourier-Transform Infra-Red spectroscopy (FTIR). It was revealed that the catalyst has BET surface area of 430 m2 /g, 0.254 cc/g total pore volume, 60% carbon content, and surface functional groups that include nitriles, alkenes and aromatics at low intensity. The batch experiment on AN removal showed the best catalyst dosage in this system is 0.5 g while 90 spm shaker speed resulted in the highest AN removal. The initial AN concentration adversely affected the performance of the catalyst where the higher the concentration, the lower the removal. Between pseudo-first and pseudo-second order kinetic models, the latter exhibited the best fit to the experimental data explaining the mechanism of AN removal is attributable to chemisorption. The photocatalyst supported over biomass carbon has larger BET surface area compared to the conventional titaniabased photocatalyst and the system could be further improved to cater higher concentration of AN for practical applications.